A evolução do conceito de governança corporativa à luz da ética: uma análise longitudinal - Berardi, Patricia Calicchio (2008)
The theme of corporate governance is no novelty. Since the 1930’s scholars have investigated the theme, pursuing to understand the relationships between management practices and maximization of wealth, legal structures and shareholders’ effective control and management’s responsibilities, among other issues. Corporate governance is based on principles such as disclosure, fairness, accountability and ethics. However, it seems little has been studied about ethical principles of governance in the field of Business Administration. The objective of this study is to perceive the academic production characteristics related to corporate governance based on business ethics vision. It was based in the content analysis of state-of-the art literature in the field of corporate governance with the objective of tracing the evolution of the concept of corporate governance. The results indicate there is growing production of studies on corporate governance in the fields of General Business Administration and Finance, with little focus on ethic issues, with a pragmatic and less theoretical approach. Therefore, there is a space to be explored and theory to be developed within the field of corporate governance in what concerns the construction of business ethics values within the field of Business Ethics.